Identification and characterization of a target antigen recognized by the monoclonal antibody against Opisthorchis viverrini - Anchalee Techasen; Chanika Worasith; Duangkamon Muengsaen; Jiraprapa Ponglong; Panupong Mahalapbutr; Napat Kongtaworn; Thanyada Rungrotmongkol; Kanoknan Khongsukwiwat; Phattharaphon Wongphutorn; Chompunoot Wangboon; Chutima Homwonk; Sujittra Chaiyadet; et al. (PLoS ONE, 2025)
Opisthorchis viverrini (Ov) infection caused opisthorchiasis, which posed an important risk for the development of cholangiocarcinoma (CCA). Therefore, it is crucial to focus on the primary prevention and control of opisthorchiasis in order to control CCA effectively in Thailand and other endemic regions. A recent diagnostic method of antigen detection using monoclonal antibody-based enzyme-linked immunosorbent assay (mAb-ELISA) has the potential for rapid mass screening of opisthorchiasis. Nevertheless, the specific antigen(s) in Ov adult worms recognized by mAb have not been determined. In this study, we aimed to identify and characterize the target molecule of our in-house Ov-specific monoclonal antibody (mAb KKU505). The specific antigenic band formed by the reaction of Ov adult worm extract and mAb KKU505 was detected using western blot analysis. The protein band was identified as the myosin heavy chain of Ov using LC-MS/MS analysis. The reactivity of the recombinant full-length myosin heavy chain (rMHC) was comparable to that of the crude Ov antigen when evaluated using mAb-ELISA at similar protein concentrations. Moreover, the binding ability between Ov myosin head domain and mAb KKU505 was confirmed using in silico analysis. The results reported here indicate that rMHC could potentially substitute for Ov crude antigen in antigen detection by mAb-ELISA and as a positive control for Ov-strip in lateral flow assays, thereby avoiding the use of laboratory animals for the production of Ov adult worms.